Bilateral primary ovarian Ewing sarcoma recurring as left submandibular lymphadenopathy diagnosed on cytology - Shaivy Malik; Neha Kawatra Madan; Meetu Agrawal; Rajni Yadav; Adarsh Barwad (University of São Paulo, 2024)
Ewing sarcoma (ES) is a highly malignant and aggressive small round-cell tumor originating from primitive neuroepithelium and mesenchymal stem cells. It is usually seen in children and adolescents with a male predilection and a preponderance to occur in long bones. Although skeletal/soft tissue ES is encountered in clinical practice, primary ES of the genital tract, particularly bilateral primary ovarian ES, is highly uncommon, with only a handful of cases reported worldwide. Ovarian ES is occasionally reported to involve para-aortic and pelvic lymph nodes in advanced stages. Still, cervical lymph node metastasis from ovarian ES is an infrequent clinical occurrence and, when present, indicates a worse prognosis. Here, we present an intriguing case of bilateral peripheral primary ovarian ES in an adult female, recurring as metastasis in the left submandibular lymph node. This case underlines the importance of keeping metastasis from ES as a possible differential while diagnosing metastatic small round cell tumors in peripheral lymph nodes. It also highlights the usefulness of a minimally invasive diagnostic modality of fine needle aspiration cytology and cell block preparation with applied ancillary techniques of immunohistochemistry and confirmatory molecular testing by fluorescence in-situ hybridization (FISH), for an accurate and quick diagnosis of such entities. The cytological diagnosis of our patient helped in the prompt and early initiation of chemotherapy without requiring any invasive procedure.